Targeting tumor cells using magnetic nanoparticles – a feasibility study in animal models. Issue 7 (3rd October 2022) - Goren, Koby; Neelam, Neelam; Yuval, Jonathan B.; Weiss, Daniel J.; Kunicher, Nikolai; Margel, Shlomo; Mintz, Yoav
Abstract: Introduction: In non-resectable tumors, chemotherapy is crucial to improve patient survival. However, it is often accompanied by considerable side effects. Targeted delivery of chemotherapy by coupling with iron oxide superparamagnetic nanoparticles (IONP) could potentially increase efficacy while decreasing adverse systemic side effects. We aimed to evaluate the feasibility of targeting nontoxic, biodegradable-IONP into tumors in-vivo by applying an external magnetic field. Material and methods: Subcutaneous colon carcinoma tumors were induced in 35 mice. IONP was injected systemically, followed by suturing of a magnet on top of the tumors for 2–24 h. Tumors and livers were excised and stained for iron to explore IONP localization. Results: Iron staining was evident in 43% and 20% of tumors exposed to magnets for 4 h or 24 h, respectively. No iron was present following 2 h exposure, nor in the control group; however, iron stain in the livers indicates most of the IONP were cleared by the liver 24 h later. Conclusion: We demonstrated the targeting feasibility of IONP to tumor tissue by an external magnetic field. Our data shows successful targeting; however, with low efficacy following systemic injection of the IONP. As such, a paradigm shift is strongly recommended from systemic to locoregional IONP injection to increase targeting efficacy.